User selection and resource allocation algorithm with fairness in MISO-OFDMA - Papoutsis, Vasileios D.; Fraimis, Ioannis G.; Kotsopoulos, Stavros A. (IEEE communications letters, 2010)
The problem of user selection and resource allocation for the downlink of wireless systems operating over a frequency-selective channel is investigated. It is assumed that the Base Station (BS) uses many antennas, whereas a single antenna is available to each user. A suboptimal, but efficient algorithm is devised that is based on Zero Forcing (ZF) beamforming and on spatial correlation. The algorithm maximizes the sum of the users' data rates subject to constraints on total available power and proportional fairness among users' data rates. The main feature of it is the proportionality among users' data rates which is guaranteed as it is shown by simulations.